Georfrey Sy graduated summa cum laude - Sy, Georfrey (Animo Repository, 2000)
Computer Science major in Software Technology Georfrey Sy graduated summa cum laude. He was also inducted as a member of the Jose Rizal Honors Society during the Commencement exercises for being on the Dean's first honors list throughout his stay in the University.